Effect of insulin degludec versus insulin glargine on glycemic control and daily fasting blood glucose variability in insulin-naïve Japanese patients with type 2 diabetes: I'D GOT trial. (August 2017) - Aso, Yoshimasa; Suzuki, Kunihiro; Chiba, Yasuko; Sato, Minoru; Fujita, Nobuya; Takada, Yoshihisa; Murano, Shunichi; Kuroda, Hisamoto
Highlights: Insulin degludec reduces the within-subject day-to-day variability of fasting blood glucose. Insulin degludec significantly lowers fasting pre-breakfast blood glucose than insulin glargine. Treatment with insulin degludec or glargine achieved similar improvement in glycemic control. Abstract: Aims: Insulin degludec (IDeg) is an ultra-long-acting insulin that has a smooth time/action profile over more than 42 h. The present study compared the effects of IDeg and insulin glargine (IGlar) on HbA1c reduction and on within-subject day-to-day variability of fasting blood glucose (FBG) in insulin-naïve patients with type 2 diabetes. Subjects and methods: Eligible patients were randomly allocated at a 3:1 ratio to receive once-daily IDeg ( n  = 31) or IGlar ( n  = 12). Both basal insulins were administered before breakfast and titrated to achieve a target FBG <110 mg/dl. The primary endpoints were the change in HbA1c from baseline to 24 weeks of treatment, as well as the standard deviation (SD) and coefficient of variation (CV) of FBG from 8 to 12 weeks and from 20 to 24 weeks. Secondary endpoints included the QOL evaluated by the Diabetes Therapy-Related QOL questionnaire. Results: After 24 weeks, HbA1c was decreased by 1.6% in the IDeg group and 1.7% in the IGlar at the same insulin dosage. At 24 weeks, FBG was significantly lower in the IDeg group than in the IGlar group and the CV of FBG was significantly smaller in the IDeg group. The frequency of total and severe hypoglycemic episodes did not differ between the groups. In the IDeg group, QOL showed significant improvement regarding anxiety and dissatisfaction with treatment. Conclusions: Treatment with IDeg or IGlar achieved similar improvement in glycemic control in insulin-naïve patients with type 2 diabetes. The day-to-day variation of FBG was smaller in patients receiving IDeg.